2016
DOI: 10.1111/jbi.12843
|View full text |Cite
|
Sign up to set email alerts
|

Does population distribution matter? Influence of a patchy versus continuous distribution on genetic patterns in a wind‐pollinated shrub

Abstract: Aim Uniform spatial population distributions are predicted to result in lower among-population genetic differentiation and higher within-population genetic diversity than naturally patchy distributions, but there have been surprisingly few attempts to isolate this effect from confounding factors. We studied the widespread wind-pollinated shrub Allocasuarina humilis that is common in a geologically stable landscape characterized by long-term population persistence to test the influence of semi-continuous versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…This has been demonstrated in a few recent studies on plants and birds. Two comparative studies on plants find that semi‐continuously or continuously distributed populations have lower genetic differentiation than patchily distributed populations (Levy et al, ; Llorens et al, ). Robin, Vishnudas, Gupta, and Ramakrishnan () studied an entire community of montane birds of the Western Ghats in India and found, with a few exceptions, highest genetic differentiation in montane‐restricted species, while the widespread species showed no genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been demonstrated in a few recent studies on plants and birds. Two comparative studies on plants find that semi‐continuously or continuously distributed populations have lower genetic differentiation than patchily distributed populations (Levy et al, ; Llorens et al, ). Robin, Vishnudas, Gupta, and Ramakrishnan () studied an entire community of montane birds of the Western Ghats in India and found, with a few exceptions, highest genetic differentiation in montane‐restricted species, while the widespread species showed no genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Density of linear features offered high resistance to jungle cat gene flow, though the model fit was very poor. Density of linear features (highway, rivers and canals) has been shown to influence genetic connectivity of roe deer ( Capreolus capreolus , Coulon et al, ) and has also been shown to affect abundance (Beazley, Snaith, Mackinnon, & Colville, ; Boulanger & Stenhouse, ) and occurrence (Wasserman, Cushman, Wallin, & Hayden, ) of mammals, which in‐turn can impact genetic differentiation in a landscape (Llorens et al, ; Weckworth et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected, in part, in the genetic analysis, where genetic variation due to differences among individuals within sampling sites across the Colorado Plateau was fairly high (PhiPT = 0.15). This level of within-population genetic diversity has been documented in other wind-pollinated species, even within populations that occupy fragmented habitat (Gray et al, 2014;Llorens et al, 2016). This same model could be bolstered with genetic and cytotypic patterns across environmental gradients to help delineate the most appropriate seed transfer zones.…”
Section: Implications For Restorationmentioning
confidence: 67%
“…Fragmented populations typically have few prospects for long-distance seed dispersal and may exhibit restricted gene flow (Anderson, 2003), though gene flow could be expected to remain high even in patchy environments due to long-distance wind dispersal of pollen (Llorens et al, 2016). Bouteloua gracilis is also evidently an autopolyploid across the study region, with diploid, tetraploid, and mixed cytotype sites distributed across the Colorado Plateau (Butterfield & Wood, 2015).…”
Section: Study Speciesmentioning
confidence: 99%